PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL PEMODERASI - Ni Ketut Santya Dewi; Ni Wayan Alit Erlinawati (Hita Akuntansi dan Keuangan, 2020)
Thisi study aims to obtain empirical evidence of thei effect of profitability and leveragei on taxi avoidancei with thei corporatei sociali responsibilityi disclosure as moderating variabeli. Thisi study focuses on consumer goods companies listed on thei Indonesia Stock Exchange, there companies produce consumer goods that are routinely needed by thei community. thei sample are 17 companies with purposive sampling technique, analysis technique used is Moderated Regression Analysis (MRA). thei results of thisi study indicate that profitability has a positive effect of taxi avoidancei. Thisi means that thei higher thei profitability, thei higher thei taxi avoidancei of thei company. Leveragei has a negative effect on taxi avoidancei. Thisi means that thei higher thei interest expense thei company has, thei lower thei taxi avoidancei rate. Corporatei sociali responsibilityi disclosure cannot moderate thei effect of profitability and leveragei on taxi avoidancei.